Optimising Natural Dyeing of Cotton with Butea Monosperma Through Anodic Pretreatment and Eco-Friendly Auxiliaries (Journal of Fiber Bioengineering and Informatics, 2025)
This study investigates the combined effect of anodic pretreatment and varying auxiliary formulations on the dyeing performance of cotton fabric using a natural dye extracted from Butea monosperma flowers. While past studies have examined the role of mordants and pH modifiers in natural dyeing, limited attention has been given to how auxiliary systems interact with electrochemically modified fabrics to influence colour yield and fastness performance. This research addresses that gap by evaluating how anodically pretreated cotton responds to common dyeing auxiliaries—sodium chloride (NaCl), potassium aluminium sulfate (alum), sodium carbonate $({\rm Na_2 CO_3}),$ and calcium oxide (CaO)—in terms of shade development, chromatic richness, and durability.Using the CIE Lab colour system, significant colour variations were observed across all treated specimens (2–7) compared to the salt-only control (specimen 1). $∆{\rm E}$ values ranged from 12.49 to 19.95, with the highest chromatic shift seen in the ${\rm NaCl}$ + alum sample, which produced a vivid orange hue with enhanced redness and yellowness. Combinations of alum and alkalis yielded deeper, more saturated shades, while alkali-only formulations produced earthier tones with moderate lightness. These outcomes highlight the synergistic effect of anodic surface activation and auxiliary chemistry on improving dye-fibre interactions.Fastness tests, conducted according to ISO 105-C10 and ISO 105-X12 standards, revealed moderate washing durability (colour change ratings of 3 to 4) and good rubbing fastness (ratings up to 4). Specimens treated with mordants and alkalis generally exhibited improved fixation and reduced staining, whereas anodic treatment enhanced surface adhesion of the dye.This study demonstrates a promising, low-impact approach to improving natural dye uptake and fastness on cotton fabric by integrating anodic pretreatment with accessible auxiliary systems. The findings support the development of sustainable, decentralised dyeing processes using locally available plant waste, with particular relevance for rural craft and textile communities seeking eco-friendly alternatives to synthetic dyes.
Keywords: Butea monosperma; natural dyeing; anodic pretreatment; cotton fabric; dye auxiliaries; colour fastness; sustainable textiles; rural textile innovation